Analysis of the Costs of Traffic Accidents in the City of Dili, Timor-Leste - Guterres, Joao Antonio; Kusuma, Andyka; Siregar, Martha Leni (Transpublika Publisher, 2025)
The Value of Statistical Life (VSL) of residents in Dili City, Timor-Leste is examined in this research using the Willingness to Pay (WTP) method to determine how the public values reducing the risk of fatal traffic accidents. Data collection involved conducting structured face-to-face interviews in various offices and schools. Each respondent was presented with three hypothetical traffic safety programs offering risk reductions of 20%, 50%, and 65%. The associated WTP amounts were USD 12, USD 15, and USD 20, respectively. VSL was computed by dividing WTP by the corresponding percentage of risk reduction. The data were further analyzed using a binary logistic regression model, executed in R Studio software, to estimate the probability of WTP based on socioeconomic variables such as gender, age, education level, occupation, income, and cost of the proposed intervention. The regression results demonstrated a statistically significant and negative relationship between the program’s cost and the willingness to pay, indicating that greater expenses lowered public acceptance. The average individual VSL was calculated at USD 524.83 for female respondents and USD 398.07 for males. Using official records of 102 traffic-related fatalities in Dili during the 2022–2024 period, the Social Value of Statistical Life (SVSL) was estimated at USD 17,830.70 for females and USD 13,524.02 for males. Based on these findings, six policy recommendations are proposed: improved road infrastructure, strengthened law enforcement, public safety education, clearer traffic signage, adequate street lighting, and enhanced pedestrian protection.